The effects of waste polyethylene terephthalate as an aggregate coating on the properties of bituminous mixture for road making - Amanina Farhana, Ahmad (2017)
Utilization of waste plastic in road making is nowadays considered as one of the positive options available to improve the quality of the bituminous mixture and also help to reduce plastic pollution in the environment. Plastic bottles are mainly composed of polyethylene terephthalate (PET). PET has many uses and is commonly used in processes such as packing and protecting. PET is considered a non-biodegradable material but it can also contribute to environmental problem when disposed in large quantities. Therefore, the growing quantities of waste should be reduced by reusing them for other useful applications. This research has examined the effects of using PET in a road making application by investigating its potential prospect in improving bituminous mixture properties. By using dry process, this research sought to determine the optimum percent of PET content that should be added to coat the aggregate and its effects on the properties of the bituminous mixture compared to those of the conventional mixture. PET was introduced in bituminous mixture in shredded forms between 2 mm and 5 mm. By using Marshall mix design method, 15 samples were used to determine the optimum bitumen content (OBC) followed by 25 samples to test the modified mixture properties and to find optimum PET content. The OBC was found to be 4.8% by weight of bituminous mixture and it was assumed as optimum binder content. PET of 2%, 5%, 10%, 15% and 20% by weight of the 4.8% OBC were tested. The results showed that 10% of PET would be the recommended optimum PET content because this level indicated good stability with 16.824kN, 2.32g/cm3 bulk density, voids filled with bitumen (VFB) with 71.35%,flow with 3.2248mm, air voids (AV) with 4.53%, and voids in the mineral aggregate (VMA) with 15%. Optimum modified mixture which consist 10% of PET has 15.23% higher stability value and 21.39% higher compressive strength compared to the conventional mixture. The outcomes showed that PET modifier would give better engineering properties and that all results analysed from the data adhered to the specifications of the Standard Specification of Road Work (SSRW) in Malaysia. In conclusion, 10% of PET by the weight of binder content is suitable to be used as aggregate coating to improve the bituminous mixture properties subjected to the right amount of addition. This finding helps to save cost of making pavement about 10% for the future development and to maintain the road in a long run.